2018
DOI: 10.1038/s41598-018-30928-2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and biogeochemistry of asphalt seeps in the North São Paulo Plateau, Brazilian Margin

Abstract: An initial multiple biogeochemical dataset was acquired from the first discovered asphalt seeps in the Brazil margin during deep-sea dive surveys in 2013 using a manned submersible. These surveys were conducted on the outer escarpment of the North São Paulo Plateau. Sediment cores taken from the submersible were processed for pore water and sediment biogeochemistry. The silica concentration, as a chemical geothermometer, showed a steep gradient in the pore water, which indicates the possibility of an active br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Comparison of TAMOC predictions with laboratory observations reported by Pesch et al23,37 for live and dead oil droplets (Experiments[1][2][3][4][5][6][7][8][9][10][11][12]. Also shown are model values when assuming suppressed aqueous dissolution of methane.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Comparison of TAMOC predictions with laboratory observations reported by Pesch et al23,37 for live and dead oil droplets (Experiments[1][2][3][4][5][6][7][8][9][10][11][12]. Also shown are model values when assuming suppressed aqueous dissolution of methane.…”
mentioning
confidence: 95%
“…Petroleum fluids comprising gaseous and liquid phases may enter deep water through natural seeps, small-scale leaks during industry operations, leaking abandoned wells, , or major accidents such as the Deepwater Horizon disaster . During such events, the coupled chemical and physical dynamics of the released gaseous and live liquid petroleum phases largely determine the trajectories and fates of these fluids in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Most seeps at continental margins are dominated by the seepage of biogenic and thermogenic methane (Claypool & Kvenvolden, ; Suess et al ., ; Suess, ). However, many hydrocarbon seeps have been discovered that are characterized by expulsions of crude oil (Estes et al ., ; Kennicutt et al ., 1988a; MacDonald et al ., ; Kvenvolden & Cooper, ; Joye et al ., ; Körber et al ., ; Jiang et al ., ). Such seeps are ideally suited to study the impact of oil seepage on the diversity, activity and distribution of microbial communities, as well as the role of oil seepage and its subsequent degradation for carbonate authigenesis (Naehr et al ., ; Orcutt et al ., ; Birgel et al ., ; Schubotz et al ., 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…During the cruise that explored the deep seafloor of the North São Paulo Plateau in Espírito Santo Basin (2500-3600 m), asphalt seeps were found at a depth of 2,700 m colonized by non-chemosynthetic megafaunal organisms [12]. They also found that, in non-asphalt seeps areas, outcrops of mudstone were covered by black manganese oxide crusts and nodules were also present [12, 13, 14]. These two particular conditions of the study area may be important factors determining patterns of bacterial diversity.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study carried out by the Iatá-Piúna consortium [13] using PCR-DGGE method found high and widespread dominance of Proteobacteria and Firmicutes at sediment samples, including asphalt seep area. The two predominant species were Erythrobacter citreu s strain VSW309 detected in hydrothermal vents and Thalossospira xianhensis strain MT02 a hydrocarbon-degrading marine bacterium.…”
Section: Introductionmentioning
confidence: 99%